Dynamic Responses of an Underground Opening Subject to Impact Loadings in Blocky Rock - Nie, Wen; Yong, Zhaorui; Ma, Guowei; Liu, Dongqiao; Fan, Lifeng; Sun, Jie (Rock mechanics and rock engineering, 2024)
The stability of rock blocks near the underground opening may be influenced by the impact loadings caused by either natural hazards or man-made disasters. This paper addressed the dynamic response of the rock blocks under impact loadings. The experimental tests were carried out to record the movement as a function of vibrations using the impact-induced rock burst system. Granite blocks were placed in the steel frame and loaded to the designed quasi-static condition at first. Permanent jumps of displacements toward the opening were observed after the pulse loading was applied. Analytical investigations were carried out to understand the macroscopic friction during the vibration progress. The results showed that the friction force was reduced by 4% due to the pulse loading in the orthogonal direction. The friction angle at the block boundary was also determined and further adopted in the DDA models which were built to understand the micro-friction. Three zones were determined in the model based on the uneven distributions of stresses in the potential sliding block: the concentration zone, the transition zone and the active zone, from the opening to the inner place. Consequently, the variations of stress and displacement as the function of the vibrations in the three distinguished zones were presented to show the dynamic response of the stressed rock block. The results showed that the direction of the major principal stress was turning to be vertical in the concentration zone which was favorable for self-stabilization during the impact loading. Highlights Dynamic responses of stressed rock blocks were tested. Analytical investigations were carried out to understand the macroscopic friction. DDA models were built to examine the microscopic friction.